2020
DOI: 10.1787/44bbde61-en
|View full text |Cite
|
Sign up to set email alerts
|

States of fragility and official development assistance

Abstract: This paper analyses official development assistance (ODA) to the 57 fragile contexts in the 2020 OECD fragility framework. ODA is a crucial, reliable resource for these fragile contexts and an indispensable part of their journey to sustainable development and peace. Development Assistance Committee (DAC) members spent 63% of their net, country-allocable ODA in these contexts in 2018. Striving to protect this ODA, especially in light of the economic consequences of coronavirus (COVID-19), will be important to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…(2018 [11]) found that building resilience is significantly associated with the development of fiscal institutions, including the capacity to raise tax revenue, contain current spending, lower military spending and, to some degree, increase social expenditure.…”
Section: Building Financial Resilience In Fragile Contextsmentioning
confidence: 99%
“…(2018 [11]) found that building resilience is significantly associated with the development of fiscal institutions, including the capacity to raise tax revenue, contain current spending, lower military spending and, to some degree, increase social expenditure.…”
Section: Building Financial Resilience In Fragile Contextsmentioning
confidence: 99%
“…1 International donors invest substantial proportions of their portfolios in countries classified as fragile states. Member states of the Organisation for Economic Co-operation and Development's (OECD) Development Assistance Committee (DAC) spent 63% of their net country-allocable official development assistance (ODA) on fragile contexts in 2018 (Desai, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…3 Since definitions of fragility, fragile states, and fragile contexts have changed over the past decade, it is not possible to quantify the increase in countries considered fragile. Desai shows that the OECD's States of Fragility report identified 57 fragile countries in 2020, up from 50 in 2015, and 43 in 2010 (Desai, 2020).…”
mentioning
confidence: 99%